Friend or Foe? EFL Students’ Perceptions of Artificial Intelligence in Writing Classes - Yansen Robert Kaluti Yansen; Anjar Kusuma Dewi; Andi Patmasari; Nadrun Nadrun (e-Journal of ELTS (English Language Teaching Society), 2026)
This study investigated students’ perceptions of the use of Artificial Intelligence (AI) in writing classes at Tadulako University. A mixed-methods approach was employed, combining a questionnaire with 30 students and semi-structured interviews with four participants. The questionnaire consisted of 32 items organized into six dimensions: perceived usefulness, perceived effectiveness, motivation, attitudes, challenges, and responsible use of AI. The findings revealed that students generally hold positive perceptions of AI, particularly regarding idea generation (M=4.20), process support (M=4.17), and vocabulary assistance (M=4.13). Grammar correction was identified as the most effective function of AI (M=3.97). Motivational effects were moderate, with the strongest influence on task completion (M=3.77). Students demonstrated cautious but generally positive attitudes, with more neutrality toward formal AI integration in the curriculum. Prominent challenges included concerns about over-reliance, information inaccuracy, and reliability. Encouragingly, students showed critical and ethical engagement with AI, as evidenced by high scores for information verification (M=4.07) and critical evaluation (M=4.10). These findings suggest that students perceive AI as a conditionally beneficial tool for writing support, provided it is used critically and responsibly.